Similar Inflammatory Biomarkers Reflect Different Platelet Reactivity in Percutaneous Coronary Intervention Patients Treated With Clopidogrel: A Large-Sample Study From China - Li, Jiawen; Yuan, Deshan; Jiang, Lin; Tang, Xiaofang; Xu, Jingjing; Song, Ying; Chen, Jue; Qiao, Shubin; Yang, Yuejin; Gao, Runlin; Xu, Bo; Yuan, Jinqing; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Platelet reactivity is closely associated with adverse events in percutaneous coronary intervention (PCI) patients. Inflammation plays a crucial role in the development of coronary heart disease. Aim: To investigate the association of inflammatory biomarkers such as leukocyte count and high-sensitivity C reactive proteins (hs-CRP) with platelet reactivity in PCI patients treated with clopidogrel. Method: We examined 10,724 consecutive PCI patients in Fuwai hospital from January 2013 to December 2013. High on-treatment platelet reactivity (HTPR) was defined as adenosine diphosphate (ADP)–induced platelet maximum amplitude [MA(ADP)] of thromboelastogram (TEG) > 47 mm, and low on-treatment platelet reactivity (LTPR) MA(ADP) < 31 mm. Results: Finally, 6772 PCI patients treated with clopidogrel who have the results of postoperative TEG were enrolled. Among them, 2070 (30.57%) presented HTPR and 2568 (37.92%) presented LTPR. As for LTPR, multivariate logistic regression showed that leukocyte count (OR: 1.153, 95% CI 1.117-1.191) and hs-CRP (OR: 0.920, 95% CI 0.905-0.936) were independent predictors, along with diabetes mellites, hemoglobin, platelet count and glucose. As for HTPR, multivariate logistic regression showed that leukocyte count (OR: 0.885, 95% CI 0.854-0.917) and hs-CRP (OR: 1.094, 95% CI 1.077-1.112) were independent predictors, along with sex, hemoglobin, platelet count and glucose. Conclusions: This was the first large real-world study reporting that both leukocyte count and hs-CRP were the independent factors for platelet reactivity in PCI populations treated with clopidogrel, among which higher leukocyte count associated with more LTPR while higher hs-CRP associated with more HTPR, providing new insights on individualized antiplatelet therapy.